Anti-inflammatory effect of 3, 7-dimethyl-1, 8-hydroxy-6-methoxyisochroman via nuclear factor erythroid 2-like 2-mediated heme oxygenase-1 expression in lipopolysaccharide-stimulated RAW264.7 and BV2 cells. (4th March 2019) - Ko, Wonmin; Quang, Tran Hong; Sohn, Jae Hak; Yim, Joung Han; Kang, Dae Gill; Lee, Ho Sub; Kim, Youn-Chul; Oh, Hyuncheol
Abstract: Objective: The isochroman-type fungal metabolite 3, 7-dimethyl-1, 8-hydroxy-6-methoxyisochroman (DMHM) was isolated from the extracts of a marine-derived fungal strain of Penicillium sp. SF-6013. In this study, we investigated the effect of DMHM on inflammatory response. Materials and methods: Anti-inflammatory effects of DMHM were examined in lipopolysaccharide (LPS)-stimulated RAW264.7 and BV2 cells. We observed their anti-inflammatory effects by ELISA, qRT-PCR, and western blot analysis. Results: DMHM revealed that it suppressed the production of prostaglandin E2 (PGE2 ), nitric oxide (NO), cyclooxygenase-2 (COX-2), and inducible NO synthase (iNOS) in LPS-stimulated RAW264.7 and BV2 cells. Furthermore, DMHM decreased the mRNA expression of pro-inflammatory cytokines including interleukin (IL)-1β and IL-6. Therefore, DMHM was further investigated to elucidate the mechanisms of its anti-inflammatory properties; the results indicated that its effect was mediated by the suppression of the nuclear factor (NF)-κB and c-Jun N-terminal kinase (JNK) MAPK pathways. Furthermore, the anti-inflammatory activity of DMHM correlated with its induction of heme oxygenase-1 (HO)-1 expression via activation of the nuclear factor erythroid 2-like 2 (Nrf2) pathway. Discussion and conclusions: Collectively, the results of this study suggest that DMHM inhibited several inflammatory pathways including the NF-κB and MAPK pathways, and induced Nrf2-mediated HO-1 expression, demonstrating its potential usefulness for treating inflammatory and neuroinflammatory diseases.